Multiple loop structures critical for ligand binding of the integrin α4 subunit in the upper face of the β-propeller mode 1 - Irie, Atsushi (The National Academy of Sciences of the USA, 1997)
A non-I-domain integrin, α4β1, recognizes vascular cell adhesion molecule 1 (VCAM-1) and the IIICS portion of fibronectin. To localize regions of α4 critical for ligand binding, we swapped several predicted loops within or near the putative ligand-binding site of α4 (which spans repeats 2–5 of the seven N-terminal repeats) with the corresponding regions of α5. Swapping residues 112–131 in repeat 2, or residues 237–247 in repeat 4, completely blocked adhesion to immobilized VCAM-1 and connecting segment 1 (CS-1) peptide. However, swapping residues 40–52 in repeat 1, residues 151–164 in repeat 3, or residues 282–288 (which contain a putative cation binding motif) in repeat 5 did not affect or only slightly reduced adhesion to these ligands. The binding of several function-blocking antibodies is blocked by swapping residues 112–131, 151–164, and 186–191 (which contain previously identified residues critical for ligand binding, Tyr-187 and Gly-190). These results are consistent with the recently published β-propeller folding model of the integrin α4 subunit [Springer, T. A. (1997) Proc. Natl. Acad. Sci. USA 94, 65–72], in which seven four-stranded β-sheets are arranged in a torus around a pseudosymmetric axis. The regions of α4 critical for ligand binding are adjacent to each other and are located in the upper face, the predicted ligand-binding site, of the β-propeller model, although they are not adjacent in the primary structure.